The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1248/bpb.b12-00254
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Adipogenesis by Kaempferol, a Component of <i>Rhizoma Polygonati falcatum</i> in 3T3-L1 Cells

Abstract: Rhizoma Polygonati falcatum (RPF) has been used as a traditional herbal medicine in Asia, because of its anti-hyperglycemic, anti-triglycemic, and anti-tumor activity. In this study, we determined the antiadipogenic potential of RPF extract and its component kaempferol in 3T3-L1 adipocytes, and the underlying molecular mechanism(s) using microarray analysis. Adipocyte differentiation of 3T3-L1 cells was significantly impaired by RPF extract and kaempferol as monitored by Oil Red O staining and quantitative mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 40 publications
0
35
0
1
Order By: Relevance
“…Several plant extracts and compounds that show an inhibitory effect on body weight gain via suppression of PPARγ expression have been reported (2427). As previously suggested, kaempferol, a type of flavonol shown to be a PPARγ antagonist, exerts its anti-obesity effects partly through the down-regulation of PPARγ (28). BBR potently inhibits the differentiation of 3T3-L1 preadipocytes by inhibiting the mRNA and protein levels of PPARγ and C/EBPα and their upstream regulators (29).…”
Section: Discussionmentioning
confidence: 93%
“…Several plant extracts and compounds that show an inhibitory effect on body weight gain via suppression of PPARγ expression have been reported (2427). As previously suggested, kaempferol, a type of flavonol shown to be a PPARγ antagonist, exerts its anti-obesity effects partly through the down-regulation of PPARγ (28). BBR potently inhibits the differentiation of 3T3-L1 preadipocytes by inhibiting the mRNA and protein levels of PPARγ and C/EBPα and their upstream regulators (29).…”
Section: Discussionmentioning
confidence: 93%
“…26) H460, H1299, and A549 cells were seeded in 96-well plates at a density of 3000/well for 24 h, and treated with different concentrations of quercetin (0-200 µm) for 72 h. Cells were then incubated with MTT reagent (2 mg/ mL, 50 µL) for 4 h. The effect of quercetin on cell proliferation was measured by incubating cells with 50 µm quercetin at different time points. The fraction of living cells was measured using an enzyme-linked immunosorbent assay plate reader as the optical density at 540 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Another plant species, Aspalathus linearis , contains quercetin as a major component and inhibits adipogenesis and the accumulation of triglycerides in adipocytes [31]. Studies carried out with kaempferol revealed that this flavonoid reduces adipogenesis in 3T3-L1 cells [32]. In addition, Bhattacharya et al [33] demonstrated that flower extracts containing quercetin and kaempferol reduced the accumulation of fat in Caenorhabditis elegans, a model for obesity.…”
Section: Discussionmentioning
confidence: 99%